The Effectiveness Of The Implementation Of Finger Print Attendance On Employee Attendance Discipline At Pt. Kalibaru - Sawet (PT. Anagata Sembagi Education, 2024)
Fingerprint attendance has only been applied in the past few years at the PT Kalibaru office. However, there are still several acts of violating the rules carried out by employees who do not comply, such as not being in the office when it is still working hours, coming and leaving work not based on working hours and coming only to fill in absences and then leaving the office. The purpose of the study was to analyze the effectiveness of the use of fingerprint attendance on employee attendance discipline at PT Kalibaru. The research method uses a quantitative method with a sample of 110 respondents. The data collection technique uses a questionnaire. The results of the study found that the application of fingerprint attendance was quite effective in encouraging compliance with employee attendance discipline as evidenced by sig. 0.000> 0.05. The contribution given from the influence of fingerprint attendance (X) on employee attendance discipline (Y) = 20.8%, the remaining 79.2% was influenced by other variables outside the research carried out.